Technique and tactics of competitive activity in classical skiing sprint during the XXIIIrd Olympic games 2018 (OG-2018) - Batalov, A. G.; Burdina, M. E.; Lunina, A. V.; Shchukin, A. V. (The Russian Journal of Physical Education and Sport, 2018)
Abstract: Further professional sport development is connected with many-sided analysis of competitive activity, demonstrated by the leaders-winners and prizewinners of the most important International competitions - the Olympic Games (OG) and World Championships (WC). It helps to see the tendencies of competitive activity development and realize effective training programs projection. Materials. Competitive activity technique and tactics characteristic in classical skiing sprint during the OG-2018. Research methods. Information sources analysis, rout relief, scoresheets analysis, video analysis using Coachs eye+ program, methods of mathematical statistics. Results. Overcoming the climb with the alternating two-step classical walk using "ski race" technique provides great movements frequency and speed increase at this stages of the rout. The key point of the competition is "breaking off" tactics use during the second distance rise. The tactics of leading in terms of great competition between finalists is not optimal. Conclusion. Prizewinners` technique-tactical actions analysis in classical sprint during the OG-2018 helped to reveal modern tendencies, which provide effective competitive activity, can be used during training and competitive programs realization and projection among highly-qualified skiers-sprinters.